South-western federal taxation 2022 : corporations, partnerships, estates & trusts / William H Hoffman ...[et al] - Hoffman, William H.
Master the latest tax law and recent changes impacting corporations, partnerships, estates and trusts and financial statements with SOUTH-WESTERN FEDERAL TAXATION 2022: CORPORATIONS, PARTNERSHIPS, ESTATES & TRUSTS, 45E and accompanying professional tax software. This reader-friendly presentation emphasizes the most recent tax changes and 2021 developments with coverage of the Tax Cuts and Jobs Act of 2017 and related guidance from the treasury department. Recent examples, updated summaries and current tax scenarios clarify concepts and help sharpen critical-thinking, writing and research skills, while sample questions from Becker C.P.A. Review help you study. Each new book includes access to Intuit ProConnect tax software and Checkpoint (Student Edition) from Thomson Reuters as well as CNOWv2 online homework tools. Use these resources to prepare for the C.P.A. exam or Enrolled Agent exam or to launch a career in tax accounting, financial reporting or auditing.